(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research deals with the history of song and music in Sulaimani, from the beginning of its establishment to the last decade of the twentieth century (1784-1990). This paper consists of three parts, conclusions and a list of references, The first part is the introduction which contains the research procedure. The second part consists of two basic discussions, each with several branches. The first discussion, the pre-registration phase, the researchers present their discussion through two pieces of evidence. The first evidence is the content of the poems about song and music, while the second evidence is the travel memoirs of the orientalists. In the second discussion, which is the post-recording stage, the researchers try to present the contributing factors that have become a factor for the embodiment and further development of the art of singing and music in Sulaimani, such as: Establishment of military flute, opening of schools and the arrival of bow machine and recording companies, establishment of radio broadcasting house, establishment of the first music institute, establishment of television, opening of music courses, establishment of musical groups in Sulaimani and Sulaimani Institute of Fine Arts etc,... The third part, the Results and, recommendations, suggestions and list of sources, also a summary of the study in English are presented.